Answer:
y = 2x - 1
Step-by-step explanation:
4x - 2y = 2
So I'm assuming that your goal is to solve for the value of y in terms of x
First: the whole equation can be divided by 2
2x - y = 1
Second: subtract 2x from both sides
-y = -2x + 1
Third: divide each side by -1
y = 2x - 1
Done! I would appreciate Brainliest but no worries.
Answer: x - 5/x + 1
Step-by-step explanation:
This algebraic fraction
The task to be performed here is factorisation and simplification. Now going by the question,
x² + 4x - 45/x² + 10x + 9, the factorisation of
x² + 4x - 45 = x² + 9x - 5x - 45
= x(x + 9 ) - 5(x + 9 )
= ( x + 9 )(x - 5 ), don't forget this is the algebraic fraction's Numerator
The second part
x² + 10x + 9 = x² + x + 9x + 9
= x(x + 1) + 9( x + 1 )
= ( x + 9 )( x + 1 ), this is the algebraic denominator.
Now place the second expression which is the denominator under the first expression which is the numerator.
( x + 9 )( x - 5 )/( x + 9 )( x + 1 ).
You can see that, ( x + 9 )/( x + 9 ) divide each other , therefore therr then cancelled and left with
x - 5/x + 1
Answer:
$693
Step-by-step explanation:
Catherine invested a principal of $1,650 in her bank account with;
interest rate of 3.1%
How much interest did she earn in 14 years?
To find the amount accumulated in the 14 years, we use the formula:
A = P(1 + rt)
Where A is the amount accumulated, P is the principal, r is the interest rate and t is the time.
A = $1650(1 +
(14))
A = $1650 + $693 = $2343
Interest = Amount (A) - Principal (P) = $2343 - $1650 = $693
Answer:
So first you have to do 12-2 since it's in parenthesis. It is 10. 5+4 is 9, and 9 times 10 is 90. 3 squared is 9, then you divide 90 by 9. The answer is 10.
Answer: frequency
Step-by-step explanation: